2019
DOI: 10.1007/s42729-019-00148-2
|View full text |Cite
|
Sign up to set email alerts
|

Movement and Retention of NH4-N in Wetland Rice Soils as Affected by Urea Application Methods

Abstract: A field experiment was conducted to investigate the dynamics of ammonium nitrogen (NH 4 +-N) in the soil during an entire ricegrowing season. The NH 4 +-N dynamics were measured in paddy soils from two N application methods, namely, urea deep placement (UDP) and broadcast prilled urea (PU). The pore water samples from a 10 cm soil depth were collected using a "rhizon sampler." The samples were collected at 0, 7, 10, 14, 20, and 22 cm from the urea briquette (UB) placement point at 7, 14, 21, 35, 64, and 83 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Maintaining the incubation temperature (25˚C) and soil moisture content around 35% water-filled pore space throughout the experiment period allowed for considerable NH 3 volatilization loss (up to 38% of applied N). These losses aligned with other studies that reported NH 3 loss of 15 to 64% of applied N from a surface applied urea-N fertilizer (San Francisco, Urrutia, Martin, Peristeropoulos, & Garcia-Mina, 2011;Siddique et al, 2020;Vaio et al, 2008). Cation exchange capacity and N 2 fixation capacity can affect soil NH 3 volatilization, likely because these soil properties control the amount of available total applied N near soil surface (Ferguson et al, 1984).…”
Section: Discussionsupporting
confidence: 87%
“…Maintaining the incubation temperature (25˚C) and soil moisture content around 35% water-filled pore space throughout the experiment period allowed for considerable NH 3 volatilization loss (up to 38% of applied N). These losses aligned with other studies that reported NH 3 loss of 15 to 64% of applied N from a surface applied urea-N fertilizer (San Francisco, Urrutia, Martin, Peristeropoulos, & Garcia-Mina, 2011;Siddique et al, 2020;Vaio et al, 2008). Cation exchange capacity and N 2 fixation capacity can affect soil NH 3 volatilization, likely because these soil properties control the amount of available total applied N near soil surface (Ferguson et al, 1984).…”
Section: Discussionsupporting
confidence: 87%
“…It seems that that the improvement in grain yield with Zn application differs with rice variety based on the response in grain weight or the number of spikelets panicle −1 . The productivity variation among rice varieties caused by N and Zn fertilizer application established in this study could be about the ability of N use efficiency, which the lower ability may result in higher rate of N loss by ammonia volatilization, especially in the waterlogged condition (Siddique et al 2019).…”
Section: Discussionmentioning
confidence: 89%
“…Brazil is the main rice producer outside the Asian continent, and about 75% of total rice production comes from the south of the country in flood irrigation areas (SOSBAI 2018). Rice cultivation in this region presents major challenges (Siddique et al 2019), especially the occurrence of diseases, which is a limiting factor for the cultivars to attain their productive potential.…”
Section: Introductionmentioning
confidence: 99%